A közösség értelmezése, jellegzetességei és területi vonatkozásai - Horváth Csilla (Egyesület Közép-Európa Kutatására Szeged, 2020)
Human communities, regardless of the number of people they are composed of, their kinships, their spatial location, or other characteristics, have always formed the basis of society. Since humans are social beings, in a healthy case, no one can become independent of the community that surrounds them. Thus, the cooperation between the person and the community is not an optional behavior. Without this cooperation, the person excludes himself or herself from the protection of the fellow human beings. However, the functioning of the community is not so self-evident. On the one hand, it is influenced by external circumstances - such as the era in which it exists, the political system, economic effects, the geographical location of coexistence and its sustainable use by the community –, as well as the identity, mentality, education and responsibility of the individuals composing the community, towards their fellow human beings and towards the entire community. Moreover, these aspects are constantly changing, which further complicates the existence, functioning, and interpretability of the community. In my article, I try to summarize what types of community interpretations exist, how and for what reason both the interpretations and the communities themselves changed over the course of historical ages, I also try to explore whether there is any significance of geographical space in this process, and if there is, what it is.
Keywords: Társadalomtudományok; Társadalom- és gazdaságföldrajz